2014
DOI: 10.1016/j.phymed.2014.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Kolaviron, a biflavonoid complex of Garcinia kola seeds modulates apoptosis by suppressing oxidative stress and inflammation in diabetes-induced nephrotoxic rats

Abstract: Diabetic nephropathy is a complex disease that involves increased production of free radicals which is a strong stimulus for the release of pro-inflammatory factors. We evaluated the renal protective effect of kolaviron (KV) - a Garcinia kola seed extract containing a mixture of 5 flavonoids, in diabetes-induced nephrotoxic rats. Male Wistar rats were divided into 4 groups: untreated controls (C); normal rats treated with kolaviron (C+KV); untreated diabetic rats (D); kolaviron treated diabetic rats (D+KV). A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(35 citation statements)
references
References 32 publications
3
32
0
Order By: Relevance
“…However, oral administration of biflavonoid and metformin significantly improved the antioxidant status by reducing the lipid peroxidation in the liver of diabetic rats through its antioxidative and antiperoxidative properties. Previous study proved that kolaviron, a biflavonoid which is structurally similar to our compoundbiflavonoid, modulated apoptosis by suppressing oxidative stress and inflammation in diabetes-induced nephrotoxic rats [60]. Furthermore, Ye et al [61] have already been reported that biflavonoid has anti-inflammatory and analgesic activity in carrageenin-induced paw oedema in rats.…”
Section: Discussionsupporting
confidence: 58%
“…However, oral administration of biflavonoid and metformin significantly improved the antioxidant status by reducing the lipid peroxidation in the liver of diabetic rats through its antioxidative and antiperoxidative properties. Previous study proved that kolaviron, a biflavonoid which is structurally similar to our compoundbiflavonoid, modulated apoptosis by suppressing oxidative stress and inflammation in diabetes-induced nephrotoxic rats [60]. Furthermore, Ye et al [61] have already been reported that biflavonoid has anti-inflammatory and analgesic activity in carrageenin-induced paw oedema in rats.…”
Section: Discussionsupporting
confidence: 58%
“…The unusual inflammatory response upon the renal injury during aging contributes to generation of excessive cytokines and chemokines, which in turn, ignite elaborated the molecular inflammatory pathways (Della Penna et al, ; He et al, ). Several research have shown significant increases of pro‐inflammatory mediators in the renal injury and diseases (Ayepola et al, ), suggesting that the severity of organ damage and dysfunction is positively associated with the level of pro‐inflammatory mediators. Our results showed that aging led to elevations of TNF‐α, IL‐6 and IL‐1β in the injured renal tissues and serum.…”
Section: Discussionmentioning
confidence: 99%
“…Treatments of MVR 100, 200 mg/kgBW and Glibenclamide 60 mg/kgBW significantly ameliorated the kidney architectural damage compared with the diabetic control group in a dose‐dependent fashion. Ayepola and his group revealed that isolated kolaviron biflavonoid from Garcinia kola seeds significantly suppressed the STZ‐induced nephrotoxicity via ameliorating inflammatory cytokines (IL‐1β) and renal apoptosis (TUNEL positive cell) compared to diabetic control (Ayepola, Cerf, Brooks, & Oguntibeju, ). MVR effects against HFD/STZ‐induced DN was also confirmed by apoptosis assay (reduced the TUNEL positive cell).…”
Section: Discussionmentioning
confidence: 99%